“Data my ass”: Political rhizomes of power and the symbolic violence of neoliberal governance and privatization - Rogers, Pamela; Grant, Nichole E. (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2024)
In October 2022, New Brunswick Minister of Education and Early Childhood Development Dominic Cardy publicly resigned and widely disclosed his disappointment with Premier Blaine Higgs’ leadership. Using Cardy’s unprecedented public resignation letter as a primary source, this paper explores the inner workings of neoliberal governance and privatization in public education and critically analyzes data manipulation, governance shifts, and problematic conservative “hands-offism.” Applying a rhizomatic methodological framing and theoretically drawing from Bourdieu and Passeron’s (1977) conceptualization of symbolic violence and Gilmore’s (2008) notion of “organized abandonment,” we argue that neoliberal governance and privatization disproportionately affect vulnerable communities and weaken democratic processes. To understand these complexities, we utilize a rhizomatic analysis, simultaneously considering historical and geographical contexts, governance structures, and political narratives. We conclude that neoliberal governance and privatization are inherently symbolically violent, as they are used in tandem to perpetually defund and dismantle public institutions.